How farmland circulation affects household financial vulnerability in China: The chain mediation effect of labor transfer and financial literacy - Sun, Fei; Wang, Lijun; Cao, Shouhui; Zhang, Yuan (Frontiers in Sustainable Food Systems, 2023)
Financial vulnerability is an important issue in livelihood resilience research domain. In the context of the Farmland Property Rights Reform in rural China and the promotion of farmland circulation, this study aims to explore whether and how household financial vulnerability is affected by farmland circulation and whether its impact shows heterogeneous characteristics depending on differences in farm household characteristics and regional characteristics. To answer these questions, a theoretical and empirical study was conducted based on the latest available Chinese household survey data (N = 9,822) from 2015 to 2019, using a chain mediating effects model and group regressions. The findings showed that farmland circulation could significantly reduce household financial vulnerability (Coef.=−0.167, p<0.01) while labor transfer and financial literacy played a mediating role. That is to say, farmland circulation could indirectly reduce household financial vulnerability by affecting labor transfer and financial literacy. The heterogeneity analysis showed that farmland circulation had a stronger mitigating effect on the financial vulnerability of older “first-generation farmer” households (with heads born before the 1980's) and households in the eastern regions with higher levels of economic development, suggesting that despite the “better late than never” advantage of farmland circulation, it can lead to greater regional inequality. These findings not only advance our understanding of how farmland circulation is associated with financial vulnerability but also provide some implications for the government's continuous optimization of the Farmland Property Rights Reform to ensure the financial security of farming households.